Economic Development Impacts of Urban Rail Transport - Graham Crampton (European Regional Science Association (ERSA), 2003)
New investments in urban rail transport, both in Europe and North America, have been widely discussed in the transport policy literature, especially in the context of the relative success of individual projects. Recent experience in developed countries has seen something of a revival of urban light rail infrastructure, mainly because of its lower cost relative to full underground metro rail. Among the issues raised are firstly, what are the impacts of new urban rail infrastructure on potential corridors of economic development along the new routes; and secondly, whether the access gains offered by urban rail mean that private sector contributions can partly be used to finance them. This paper reports on further progress on internationally funded comparative research first discussed at previous ERSA Conferences. It reports evidence (based on site visits) on the economic development impacts of new urban light rail. Visits to a number of light rail systems in Britain and France (with other countries planned this year) provide sharp contrasts in the economic development impacts of this form of urban infrastructure, as well as in the transport policy strategies that lie behind the various projects. The Federal Government's financial involvement in urban rail projects in the US has provided yet more contrasting examples from a highly car-oriented economy. Among the findings are that urban light rail, which has often been seen as equivalent to `bus protected from congestion', generates economic development impacts most visibly in non-residential or immature areas of cities. Fully built-up residential sections of cities often simply absorb the new service with little visible change. There may however be less visible change, even in the short term, evident in local housing markets which may advertise access to tram as a property advantage. The French cities offer the most spectacular examples of light rail being used as a `public sector access mode', specifically with reference to hospitals and university campuses. These can provide a substantial `instant market', so that even new tram systems (such as Montpellier) may be operating at capacity within a few years of opening. This contrasts sharply with cases where light rail is routed through vacant or semi-derelict areas, in the expectation (or hope) of private sector investment being generated. The 25 new urban light rail projects (not all new cities) currently proposed in Britain means that this research field is of particular policy relevance there.
Keywords: 330